Desiccant system for water production from humid air using solar energy. (October 2015) - William, G.E.; Mohamed, M.H.; Fatouh, M.
Abstract: Decentralized and remote areas suffer from fresh water shortage. A new sustainable energy technique called "Water Extraction from Atmospheric Air" is introduced as a beneficial solution for this problem. This system involves the absorption of water vapor from ambient air during the night time. Then, simultaneous desiccant regeneration and water vapor condensation during the day time will be occurred. In this study, a trapezoidal prism solar collector with four fiberglass sides is designed and constructed. This collector has multi-shelves bed (desiccant carrier) in order to maximize bed surface area inside the collector. Consequently, the absorption and evaporation surfaces are increased. The experimental work shows the effect of weather conditions in system operation for both day time and night time. The regeneration and absorption processes are discussed for each operation condition. Also, different host materials (cloth and sand) with calcium chloride solution are investigated. An illustrative comparison between different bed types is demonstrated. The results revealed that the total evaporated water for cloth and sand bed can reach 2.32 and 1.23 slit/days m 2 at initial saturation concentration (30%) of cacl2 . However, the system efficiency is 29.3 and 17.76% for cloth and sand bed, respectively. Highlights: New sustainable energy technique called "Water Extraction from Atmospheric Air" is introduced. This system involves the absorption of water vapor from ambient air during the night time. The experimental work shows the effect of weather conditions in system operation for both day time and night time. The results revealed that the total evaporated water for cloth and sand bed can reach 2.32 and 1.23 lit/day m 2 . The system efficiency is 29.3 and 17.76% for cloth and sand bed, respectively.